MASUKNYA ISLAM DI SPANYOL (Studi Naskah Sejarah Islam) - Rusniati Rusniati (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
AbstractThe history of Islam in the hemisphere has long been evidence of Islam's triumph in this hemisphere. One of them in Spain. Spain is a country that was once conquered by Islam to develop the religion of Islam in the country. When Islam entered Spain, this country experienced many rapid civilizations both from Islamic culture and education, because Spain was supported by a fertile country with high economic income. thus producing great thinkers. Spain experienced rapid development and Islamic culture and education which began with studying religious and literary sciences, then increased by studying the sciences of reason. The history of the triumph of Islam in Spain needs to be examined early in its emergence. Therefore, this study explores the history of the entry of Islam in Spain. This research is a qualitative research that describes all data found through a library approach. Literature approach is used to collect various literatures and previous documents related to the object of research. This research does not determine a location as a place of research because the study tends to be on text texts. At this stage, activities are carried out in the form of processing data obtained from documents, which will then be compiled into a study. The results of the analysis are outlined in the form of a descriptive research report. The results of the study show that the origins of the entry of Islam in Spain were inseparable from the success of Tariq ibn Ziyad's defeat of the king Roderick, so this victory became the main capital for Tariq ibn Ziyad and his forces to conquer important cities in Spain.Keywords: Islam, Spain, Cordova, Islamic History.